Antimicrobial and disinfectant susceptibility patterns of isolated gram-negative rods from the Neonatal Intensive Care Unit (NICU) of the Philippine General Hospital (PGH) - Santos, Louise C.; Villanueva, Leigh Don T. (2017)
Gram-negative rods are the most common highly-pathogenic multidrug-resistant strains found in the Neonatal Intensive Care Unit (NICU) of the Philippine General Hospital (PGH). Acinetobacter spp. and Klebsiella spp. are the predominant species colonizing patients in the said unit. The study aimed to detect the presence of gram-negative rods, specifically Acinetobacter baumannii and Klebsiella pneumoniae, and determine their antimicrobial and disinfectant susceptibility patterns. Ninety samples were obtained by swabbing 6 high-touch surfaces in the NICU. Eleven (12.2%) isolates were identified as either A. baumannii and K. pneumoniae using morphological and biochemical tests. Disc diffusion was used to determine the antimicrobial susceptibility while Broth Microdilution was employed for the disinfectants. Antimicrobial resistance of Acinetobacter baumannii revealed to be highest against amikacin and meropenem while the highest activity was exhibited by ampicillin-sulbactam. Klebsiella pneumoniae was most resistant against ampicillin-sulbactam, piperacillin-tazobactam, ceftazidime, and amoxicillin/clavulanic. Amikacin, meropenem and ciprofloxacin had the highest activity against Klebsiella pneumoniae. For the disinfectant susceptibility it was found out that the minimum inhibitory concentration of 70% ethanol, hydrogen peroxide, and sodium hypochlorite was >512 mcg/mL and for benzalkonium chloride was 64 mcg/mL.